Survei Tingkat Kebugaran Jasmani Siswa Kelas VIII di SMP Negeri 1 Bangsal - Eka Alviana Santoso; Dwi Cahyo Kartiko (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Developing self-potential through participation in physical activity is one of the school's goals for students to hone concentration, endurance, flexibility, and balance as well as coordination by increasing physical fitness in PJOK learning activities. This study aims to assess the degree of fitness of class VIII students of SMP Negeri 1 Bangsal. Quantitative techniques based on survey research were used for analysis of the resulting data. Participants were Grade VIII students of SMP Negeri 1 Bangsal in Bangsal Regency. The research sample population was class VIII students of SMP Negeri 1 Bangsal. The steps in this study included 50 meter running, vertical jumping (100 meters for men, 30 meters for women), long distance running (1000 and 800 meters respectively), and standing vertical run. jump. Based on the data collected and analyzed, only 3% of the respondents were considered to be in very good physical condition, while 40% were considered to be in bad condition, and 57% were considered to be in very bad condition. As a result, this study concluded that the physical fitness level of class VIII students of SMP Negeri 1 Bangsal was quite low. Given this analysis, it is still very far from the expectations of Physical Education goals. Besides that, the lifestyle of students at this time is relatively lacking in movement, because now all activities are assisted by the existence of mobile phones that have access to the internet.